Laboratory test for confirmation of natural attenuation in groundwater - Patterson, T.L.; Tesfay, T. (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
A large, inactive copper mine near Kingman Arizona that started operations in the 1960’s has historical groundwater impacts extending beyond the limits of mining facilities. Field investigations and engineering evaluations performed from 2016 to the present defined the conceptual hydrogeologic and hydrogeochemical site model as well as a corrective action program to address the impacts. A Corrective Action Monitoring Program (CAMP) is part of the corrective action program ultimately accepted by state regulators. The CAMP includes development of performance objectives that demonstrate that the geochemical natural attenuation mechanisms described in the conceptual site model are active and effective in protecting downgradient beneficial uses of groundwater. This paper describes the conceptual hydrogeochemical site model and geochemical attenuation mechanisms that are based on neutralizing the acidic conditions in groundwater using the native aquifer materials and the concomitant precipitation and adsorption of metals that occurs when pH increases. The paper also describes a sequential batch leach test specifically designed to confirm the attenuation mechanisms and to develop quantitative or semi-quantitative performance objectives for the CAMP. The regulator has approved the special batch leach test procedure for demonstration of the attenuation model.